The Adhesive Strength of Epoxy/Sol-Gel Materials Modified by Various Ratio of γ-Al2O3 Nanoparticles - Ali, Balhassn; May, Mousa; Wang, Heming; Akid, Robert (Journal of Coating Science and Technology, 2018)
In this study, the use of sol-gel/epoxy adhesive based on the combination of organic and inorganic components within the adhesive matrix have been studied. The combination of different amounts of ᵞ-Al2O3 nano-particles to the adhesive matrix was evaluated. Mild steel specimens were prepared for lap joints, which were cured in an oven at 200°C for 16 hours. The bond strength of the sol-gel/epoxy matrix was investigated using a universal tensile test machine. The presence of Al-OH and/or Si-OH bonds increases causing an increase in the strength of the bulk material. This process is seen through the appearance of an absorption peak shoulder which appears in the range of ~ 1088 to1100 cm-1 which corresponds to Al-O-Si or Si-O-Si. The maximum adhesive strength of composite sol-gel/epoxy adhesive recorded was 23±0.4 MPa. This was obtained when small amounts of γ-Al2O3 nano-particles (4.0 wt%), were incorporated within the matrix. However, as the level of these inorganic materials in the adhesive matrix increased further, the adhesive shear strength gradually decreased. At a high ratio of γ-Al2O3 particles, poor interfacial bonding or adhesion between the filler and the adhesive matrix is recorded. Scanning Electron Microscopy (SEM) is used to investigate the fracture surface with 4.0 wt% γ-Al2O3, the scanning shows a very small distance of cracks, suggesting the material may act as a barrier to crack propagation and thus increases the energy required for fracture.